Basic examples of linear algebra with python: Ejemplos básicos de álgebra lineal con python - Oviedo Rodríguez, Katalina (2022)
Many times during the development of a course it is really difficult (due to the rush to cover the contents) to give specific examples and applications of the theory that has been developed. This material offers a presentation of some applications or visualizations that can be developed with the contents in the basic course of linear algebra, going through matrix operations, transformations and eigenvalues and eigenvectors. The Python programming language will be used to develop these topics. Therefore, basic knowledge in programming or Python is recommended.